Competition / The Economics of Industrial Change - Auerbach Paul (Basil Blackwell, 1990)
This book provides a critique of the treatment of competition in existing work through an analysis of a wide variety of applied topics, including market delineation, firm finance, diversification and the multinational. Introduction, The Concept of Competition, Markets and Industries, The Testing of the ''Invisible Hand'' Theorem, The Managerial Revolution, Contrasting Views of the Corporation, Capital Markets and Finance and the Structure of Industry, The Changing Patterns of Firm Organization: Vertical Integration and Congomerates and Multinationals, Trends in Competition over Time: The Historical Evolution of the Industrial Structure, Perspectives and Prospects.